2017
DOI: 10.1007/s11999-016-5146-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Innervation of the Long Head of the Triceps Brachii: A Cadaveric Investigation

Abstract: Background Some leading anatomy texts state that all three heads of the triceps brachii are innervated by the radial nerve. The posterior cord of the brachial plexus bifurcates to terminate as the radial and axillary nerves. Studies have noted the presence of axillary innervation to the long head of the triceps brachii muscle, patterns different from the classic exclusive radial nerve supply. An understanding of these variations may assist the clinician in the assessment of shoulder weakness and in preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 12 publications
3
28
1
2
Order By: Relevance
“…The figure represented in Erhardt and Futterman () indicates that the branch from the axillary nerve enters the tendinous region of the LHT as was previously described by Aszmann et al (). The latter study describes that the motor branch to the teres minor gives off an articular branch at the level of the LHT insertion, and at this point a small branch to the tendinous insertion and the adjacent capsular region could be identified in 7 out of 25 specimens (Aszmann et al, ).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The figure represented in Erhardt and Futterman () indicates that the branch from the axillary nerve enters the tendinous region of the LHT as was previously described by Aszmann et al (). The latter study describes that the motor branch to the teres minor gives off an articular branch at the level of the LHT insertion, and at this point a small branch to the tendinous insertion and the adjacent capsular region could be identified in 7 out of 25 specimens (Aszmann et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Currently 22 studies cite de Sèze et al () and 12 Rezzouk et al () [NB: Table focuses mainly on studies citing de Sèze et al (); only two citations of Rezzouk et al () were found to be additionally relevant for this study]. Nanjundaiah et al (), Bertelli and Ghizoni (), Seema and Gangadhar (2015), Yılmaz et al (), Erhardt and Futterman (), and Howard () cite both de Sèze et al () and Rezzouk et al () without recognizing the identical study groups.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations